Strategi Pembentukan Akhlak Melalui Metode Keteladanan pada Mata Pelajaran Akidah Akhlak di MTI Tarusan - Rahma, Elma; Trisno, Bambang; Awida, Nono (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This research started with the author carrying out PPL at MTI Tarusan which fostered the author’scuriosity about Madrasah Tarbiyah Islamiyah Tarusan and also the strategy of MTI Tarusan teachers to shape the morals of their students as a religious school where one of the objectivies of the institution is to form students with good morals. So, from this backgraund the researcher formulated the problem, namely the strategy for forming morals through exemplary methods and also the inhibiting factors for the formation of student morals. And in this study using a qualitative approach, to collect data troughinterviews, observation and documentation. Yhe result of the research conducted by the author are the implementation or strategy of forming morals by guiding students and exemplifying morals in terms of clothing, good behavior towards students so that they can be discliplined, honest, responsible and have good morals and provide religious activities at school so that students can easily have good morals and manners. While the formation of student morals with an exemplary approach by carrying out religious activities such as greeting teachers, friend. Read the al qur’an before the lesson begins. Read the prayer together. Answering prayers after the noon cal to prayer. Following the Dzuhur prayers and dhuhaprayers in congregation and dhuha prayers at the mosgue. Celebrating 1 muharram and maulid nabi in 1 year, following thw tasmi; al qur’an.